Imaging the Rovibrational Ground State of the Helium–Neon Dimers 4He20Ne and 4He22Ne - Kruse, J.; Schröder, J.; Blume, D.; Dörner, R.; Kunitski, M. (The journal of physical chemistry letters, 2025)
The helium–neon dimer has been subject to many theoretical studies, in which the interaction potential of the helium–neon system has been calculated with ever increasing accuracy. Calculations predict that the helium–neon system supports only a few bound states, which makes the system inaccessible to standard spectroscopic techniques. Previous experiments have probed the helium–neon potential by comparing measured and predicted scattering cross sections. However, the spatial structure and energetics of the bound states of the helium–neon system have not been studied experimentally in great detail. We employ Coulomb explosion imaging (CEI) to measure the pair distance distributions of the helium–neon dimers 4He20Ne and 4He22Ne in their rovibrational ground state. For each dimer, the binding energy is extracted from the measured pair distance distribution. Additionally, the pair distance distribution provides access to the helium–neon potential.